Factors influencing net income from steers through feedlot - R.R. Schalles; K.O. Zoellner; K. Long (Kansas Agricultural Experiment Station Research Reports, 1980)
Calves that gained rapidly before going into the feedlot continued to gain rapidly on feed and were more profitable to both the cow-calf operator and the feeder. When fed to their genetic potential, large frame, heavy, young cattle were worth more to the cattle industry than light calves.
Keywords: Cattlemen' s Day; 1980; Report of progress (Kansas State University. Agricultural Experiment Station); 377; Beef; Net income; Feedlot; Steers